FYP - viewguard: screen time monitoring & alert mobile app / Muhammad Nabil Syazwan Azman - Azman, Muhammad Nabil Syazwan (2022)
Today, the computer is indispensable, and its presence has become very important and necessary in our daily life, and it has become easier for us to do many operations and activities. The computer was invented in the second half of the twentieth century and now it has become the backbone of life. However, without limiting our usage towards computer, it can cause negative health impact, physically and psychologically. Therefore, this project aims to build a mobile application and module that could monitor the user’s computer usage to avoid impacting the overall health. This system is based on Arduino board and 2 different sensors to transmit data to monitor the usage. The objective of this project is to identify, design and develop ViewGuard Mobile Application. The target users are the Malaysian computer users. Users who tested the product found that the product is beneficial and have a positive impact as it contributes towards the wellbeing of the users. To conclude, the ViewGuard mobile application clearly will promote better health towards the computer users and will improve to those who has been impacted due to prolonged usage of computers.